Environmental evaluation of proposed alternative roads to the Mohale dam - Heydenrych, Reuben (Department of Environmental and Geographical Science, 2015)
This is an academic report submitted in partial fulfilment of the degree Master of Environmental Science. It is written to demonstrate the competence of the writer in undertaking work in the field of Environmental Impact Assessment. The main purpose of the report is the comparative evaluation of two proposed alternative roads, the "Western Access Route" (WAR) and the "Least Cost Alternative Route" (LCAR). Since this is an academic report, it will not be used as a decision-making document and it will not be submitted to the proponent of the alternative roads.